Muskelfunktionsmessung mit kinetischem Oberflächen-EMG bei Kindern mit Hämophilie - Seuser, A.; Wendel, M.; Navarrete-Duran, M.; Fink, D.; Auerswald, G.; Böhm, P. (Hämostaseologie, 2011)
Electromyography (EMG) measures muscle electricity. It depends on muscle contraction and central motor control. Muscles react very sensitive on external signals (e. g. bleeding), The resulting changes can be shown in EMG.Patients, methods A first study included 51 children and young adults from Costa Rica. They underwent a clinical examination and EMG of the hip, knee and ankle joints. Resting muscle tone, maximal isometric contraction and three typical isotonic movements of the joints were measured. First step of analysis was to characterize typical pathogenic changes in the muscles and to find a corresponding physical therapy to minimize these changes.Results It showed that EMG is a good marker for muscle condition. It helps to individualize therapy and improve effectivity of physical and physiotherapeutic treatment of the locomotive system of children and young adults with hemophilia. It can help to recognize early subclinical changes and to control the outcome of therapeutic modalities.
Keywords: EMG; haemophilia; physiotherapy; quality control